FA-97, a New Synthetic Caffeic Acid Phenethyl Ester Derivative, Ameliorates DSS-Induced Colitis Against Oxidative Stress by Activating Nrf2/HO-1 Pathway - Mei, Yu; Wang, Zihao; Zhang, Yifan; Wan, Ting; Xue, Jincheng; He, Wei; Luo, Yi; Xu, Yijun; Bai, Xue; Wang, Qi; Huang, Yujie (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD) is a chronic idiopathic inflammatory disorder of gastro-intestinal tract, lacking effective drug targets and medications. Caffeic acid phenethyl ester (CAPE), a phenolic constituent derived from propolis, has been reported to be a potential therapeutic agent for IBD with low water solubility and poor bioavailability. In this study, we synthesized a new CAPE derivative (FA-97) and aimed to investigate the effect of FA-97 on DSS-induced colitis. Here, we found that FA-97 attenuated body weight loss, colon length shortening and colonic pathological damage in colitis mice, as well as inhibited inflammatory cell infiltration and expression of pro-inflammatory cytokines in colons. In addition, FA-97 reduced ROS production and MDA generation, while total antioxidant capacity both in DSS-induced colitis mice and LPS-stimulated primary BMDMs and RAW 264.7 cells were enhanced. Mechanically, FA-97 activated Nrf2 followed by increased HO-1 and NQO-1 and down-regulated nuclear levels of p65 and c-Jun, to suppress DSS-induced colonic oxidative stress. Moreover, FA-97 decreased pro-inflammatory cytokine expression and increased the antioxidant defenses in RAW 264.7 via Nrf2 activation. In general, this study reveals that FA-97 activates Nrf2/HO-1 pathway to eventually alleviate DSS-induced colitis against oxidative stress, which has potential activity and may serve as a candidate for IBD therapy.